Religious schooling in America : private education and public life - Jones, Steven L., 1971- (Praeger, 2008)
Advocates of religious schooling have frequently had to answer the charge that what they supported was un-American. In a book that is more than just a history, Jones tries to make sense of that charge by tracing the development of religious schooling in America over the last 125 years. He explores the rationale for religious schooling on the part of those who choose it for their children and in terms of its impact on communities, and he considers the arguments of those who criticize such schools for undermining efforts to promote national unity. The book focuses on the gradual embrace of secta.